PENGEMBANGAN KAMPUNG CITRUCOFFE SEBAGAI PUSAT EDUTOURISM RAMAH ANAK DI DESA JAPAN MELALUI PPK ORMAWA - Nabela, Sarah; Syifa'u, Ega Aulia; Permata, Meylisa Ayu; Utami, Mardhiyah; Ibrahim, Amar; Firdaus, Firza Maulana; Wangi, Putri Ayu Sekar; Wanabuliandari, Savitri (LPPM Universitas Flores, 2024)
Indonesia has various tourism potential, ranging from natural tourism, and cultural tourism to artificial tourism. However, some of the potential of the regions in Indonesia is still not maximally developed. Therefore, a Student Organization Capacity Building Program (PPK-ORMAWA) is needed. The Student Organization Capacity Building Program (PPK-ORMAWA) is a community service program in Japan Village through the development of Citrucoffee Village. The existence of this program aims to develop the potential of Japan Village, improve the welfare of the people of Japan Village and re-brand Japan Village which was previously designated as a tourist village. This program applies an implementation method consisting of counselling and training activities aimed at the people of Japan Village and the Japan Tourism Village Group, and finally monitoring and evaluation. Planning and preparation involved coordination with village officials, local communities, and related partners for the desired goals. The tourism village group, youth and local village government enthusiastically participated in carrying out the activities well and permitted the activities we carried out. The results obtained from the Student Organization Capacity Building Program (PPK-ORMAWA) are the creation of CitruCoffee Village tourism, which includes the Balik Cilik Area, Dance Studio and Outbound. The conclusion that can be drawn from this research is that through the Student Organization Capacity Building Program (PPK-ORMAWA), UKM BISMA developed Japan Village into CitruCoffee Village, a child-friendly-based edu-tourism center that utilizes the potential of Japan Village, namely Pamelo Oranges and Coffee. This program includes education and training for village communities and the development of child-friendly tourism facilities, with the hope of improving community welfare and introducing local culture to the younger generation.